Method for coating inner surface of heat exchanger with powdered solid catalyst

The combination method of liquid adhesive and powder mineral solid solid solution solves the problem of the inner wall coating catalyst in the inner wall of the plate -type heat exchanger, realizes the uniformity and mechanical strength of the coating, and improves catalytic activity.

CN119365261APending Publication Date: 2025-01-24ALFA LAVAL GOLBEY SAS +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380033008.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-03-23
Filing Date
2023-03-09
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The prior art is difficult to effectively coat the catalyst on the inner wall of the metal cavity of the brazed plate heat exchanger, especially during high-temperature assembly and consolidation heat treatment, resulting in problems such as uneven coating, substrate damage and intermetallic compound formation.

Method used

The combination method of liquid adhesive and powder -like mineral solid is used to form a dense catalyst coating through sedimentation and thermal treatment steps. The liquid adhesive is used to adhere to the powder -like solid, and the heat treatment is used to remove the solvent or polymerization adhesive to ensure the stability and uniformity of the coating.

Benefits of technology

The catalyst coating is efficiently deposited on the metal inner surface of the brazed plate heat exchanger, avoiding uneven coating and damage to the substrate, and improving the mechanical strength and catalytic activity of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119365261A_ABST
    Figure CN119365261A_ABST
Patent Text Reader

Abstract

The invention relates to a method for depositing a coating on the inner surface of a cavity forming a heat exchanger, characterized in that the coating comprises a liquid binder and a powder of a powdery solid, intended to be used as a catalyst for a physical-chemical reaction.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Designation of relevant technical fields

[0002] The present invention relates to the production of a coating which acts as a catalyst for physicochemical reactions on the metallic inner surfaces of brazed plate heat exchangers, in particular low-temperature heat exchangers.

[0003] Technical Problems to be Solved by the Invention

[0004] A brazed plate-wave heat exchanger is generally a heat exchanger formed of brazed plates and corrugated metal components. This type of heat exchanger produces a very compact unit with a large heat exchange surface area and a low pressure drop. This type of heat exchanger consists of a set of parallel plates between which intermediate elements, in particular corrugations or wavy structures, are inserted. These corrugations form a cavity with a metallic inner surface. The stacked plates form a stack of flat channels between them for different fluids to come into exchange relationship.

[0005] This heat exchanger is characterized by a metal inner surface forming cavities through which at least one fluid flows. The characteristic dimensions of these cavities are in the millimeter range and have a high aspect ratio (length / width ratio).

[0006] The plates and spacers of this type of heat exchanger are usually made of metal.

[0007] There are many techniques available for coating metal substrates, but most of these techniques are ineffective when coating the inner walls of a metal cavity in such a heat exchanger.

[0008] Chemical vapor deposition (CVD) uses a gaseous precursor of the coating to be produced. The precursor can be generated directly near the surface to be coated (embedded infiltration) or delivered to the surface to be coated via a gas (out of pack). When delivered via a gas, the main limitation of this technology is that the gas mixture is quickly consumed in the reactive species, resulting in non-uniform chemical composition and / or thickness, or even in the case of large structures, the absence of deposition for the surfaces furthest from the carrier gas supply.

[0009] An improvement of this method consists in using a binder consisting of the metal powder to be deposited, an inert diluent and an additive, which may be a stripping flux, as described by EP 2 956 566. The viscosity of the binder is adjusted to improve its fluidity and to be able to fill the cavity to be coated. In another variant taught by EP 3 049 545, the deposition is carried out by liquid means using an aqueous suspension comprising the metal powder to be deposited and at least one additive, which may be selected from binders, dispersants, etc., the purpose of which is to promote the wetting of the surface to be coated.

[0010] A heat-activated consolidation step is then required to extract the organic phase (debinding) and densify the coating. This operation is not always without impact on the mechanical properties of the structure to be coated, in particular if the treatment requires high temperatures.

[0011] This problem is exacerbated when the material constituting the coating to be deposited is highly reactive towards the substrate, for example when the material of the coating to be deposited is based on iron oxide and the substrate is based on aluminum, the problem stemming from the fact that the combination of these two materials is highly exothermic. In this example, it is not easy to maintain the iron oxide deposit on the surface of the aluminum-based substrate during high-temperature assembly operations, especially if the assembly is carried out by brazing.

[0012] This difficulty can be mitigated by installing a diffusion barrier to isolate the coating from the substrate during consolidation. This approach greatly complicates the manufacturing process.

[0013] Another difficulty with such coatings is the formation of deposits which grow partially damaging the substrate, especially if the consolidation heat treatment leads to the formation of intermetallic compounds between the substrate and the coating.

[0014] This is one of the major drawbacks of the regulations governing pressure vessels, the mechanical strength of which is defined on the basis of a minimum substrate thickness, which may take the form of a wall. This is particularly true if the intermetallic compounds formed between the substrate and the coating are themselves brittle, such as those in the Fe-Al system.

[0015] While in the case of conventional devices this can be easily circumvented by increasing the wall thickness, this is not conceivable for brazed plate heat exchangers, whose performance depends in part on the thickness of the walls constituting the plates and the corrugation structure. In fact, for this type of heat exchanger, the permissible wall thinning is of the same order of magnitude or smaller than the wall thickness consumed during the coating consolidation phase. Since the remaining wall thickness cannot be controlled after this fact, the precursor deposition conditions need to be perfectly controlled.

[0016] Another disadvantage of these techniques is the need to produce a completely smooth coating, without any surface roughness that would increase the reactive nature of the deposit.

[0017] To the best of our knowledge, conventional coating techniques cannot achieve adherent deposition of iron oxide on the surface of aluminum cavities with small cross-sections and large aspect ratios (greater than 1000).

[0018] Whether the deposition is performed by PVD or CVD before assembly, or after assembly using a slip, the subsequent substrate heating required for coating consolidation or assembly results in the formation of intermetallic compounds that are detrimental to the mechanical integrity of the structure, especially since these intermetallic compounds (Al-Fe) are known to be sensitive to hydrogen embrittlement.

[0019] The present invention provides new solutions to these problems. Summary of the invention

[0020] According to a first aspect of the invention, a method is proposed for producing a coating on the inner surface of a metal forming a cavity of a heat exchanger, the coating being intended to act as a catalyst for the physicochemical reaction of the normal-secondary conversion of hydrogen, the method being characterized in that it comprises the following steps:

[0021] - a step of depositing a liquid binder on the inner metal surface, the liquid binder being water-based, organic or inorganic, and

[0022] - A step of depositing a powder of a powdered solid, which is a mineral and has a particle size between 10 μm and 100 μm, on the deposited liquid binder.

[0023] The heat exchanger may be a cryogenic exchanger.

[0024] The coating (lining) obtained according to this method on the metallic inner surface of the exchanger thus acts as a catalyst for the physicochemical reactions taking place in the exchanger during its operation. The powdered mineral solid is the catalyst. In this way, the heat exchanger combines the function of a conventional heat exchanger for transferring heat between fluids with the function of a physicochemical reactor.

[0025] The liquid binder enables the powdered solid to adhere to the metallic inner surface of the exchanger, ie the mineral phase to adhere to the metallic surface.

[0026] According to one embodiment of the invention, the method comprises, after the powder deposition step, a subsequent step of maintaining the metal inner surface at ambient temperature, during which the solvent of the liquid binder is at least partially removed by evaporation.

[0027] Depending on the nature of the adhesive, for example in the case of a thermosetting adhesive, keeping the metal inner surface at ambient temperature may be sufficient to dry it and acquire all its adhesive properties. The holding time is chosen to evaporate all the solvent from the adhesive, or to evaporate a desired proportion of the solvent. This depends, in particular, on the geometrical features of the exchanger and on the nature of the adhesive. For example, a few minutes to two hours are required at a temperature between ambient temperature and 100°C.

[0028] According to another embodiment of the invention, the method according to the invention comprises a subsequent step of polymerizing the liquid binder after the powder deposition step by a heat treatment performed in a temperature range that does not allow the metal inner surface to interact with the powdered solid. Depending on the nature of the binder, for example in the case of an organic binder, polymerization may be required to dry it and obtain its full adhesive properties. The binder is selected so that polymerization can occur in a sufficiently low temperature range so that the metal inner surface of the exchanger does not interact with the powdered solid. At higher temperatures, close to the melting point of the brazing alloy used in aluminum brazed plate heat exchangers, aluminum and the brazing alloy become highly reactive with the oxide particles or mixtures of oxides, forming a powdered solid. This will have the effect of forming intermetallic compounds between the substrate and the coating and reducing the thickness of the aluminum wall.

[0029] Thus, the liquid binder used to adhere the powdered solid particles to the metallic inner surface of the exchanger is removed by evaporation or polymerizes during the heat treatment, depending on its nature.

[0030] According to one example, the heat treatment is performed at a temperature of 200° C. or less. By limiting the temperature at which the polymerization is performed to 200° C., any risk of deteriorating the mechanical properties of the aluminum is avoided and regulations are complied with.

[0031] Advantageously, a gas flow is generated in the exchanger cavity during a subsequent step of maintaining the metal inner surface at ambient temperature, during which the solvent in the liquid binder is at least partially removed by evaporation; or during a subsequent step of polymerizing the liquid binder by a thermal treatment in a temperature range that does not allow the metal inner surface to interact with the powdered solid.

[0032] For solvent evaporation at ambient temperature, the flow of gas facilitates solvent evaporation. The gas may be preheated to enhance evaporation. The gas is, for example, air or nitrogen.

[0033] Advantageously, for powders of powdered solids with a particle size between 10 μm and 100 μm, after the step of removing the powder of the powdered solids that do not adhere to the liquid binder deposited on the metal inner surface of the exchanger, a subsequent step of maintaining the metal inner surface at ambient temperature is carried out, during which step the solvent in the liquid binder is at least partially removed by evaporation; or a subsequent step of polymerizing the liquid binder is carried out by heat treatment in a temperature range that does not allow the metal inner surface to interact with the powdered solids.

[0034] After this removal, it is easier to carry out a subsequent step of keeping the metal inner surface at ambient temperature, during which the solvent in the liquid binder is at least partially removed by evaporation, or a subsequent step of polymerizing the liquid binder by a heat treatment in a temperature range that does not allow the metal inner surface to interact with the powdered solid, which would otherwise be hampered by the presence of excess powder. In fact, the presence of excess powder would form a barrier to the evaporation of the solvent and, in the case of polymerization, would increase the material that is heated unnecessarily.

[0035] According to one embodiment of the present invention, the liquid binder may be polyvinyl alcohol and / or a polymer.

[0036] Advantageously, the liquid adhesive has a viscosity comparable to that of water, i.e., 1×10 -3 Pa.s. Thus, the liquid adhesive can flow into and fill and / or pass through the exchanger cavity, covering all of its metallic inner surfaces.

[0037] Additionally, the liquid adhesive has sufficient wettability on the metal inner surface to leave an adhesive layer on the metal inner surface after the liquid adhesive contacts the metal inner surface.

[0038] The wettability and viscosity of the liquid adhesive are such that, after the liquid adhesive has flowed into the exchanger cavity, the adhesive remains on all metallic inner surfaces of the exchanger which have been in contact with the liquid adhesive and in the form of a layer of sufficient thickness.

[0039] According to the invention, the thickness of the liquid adhesive that remains adhered to the metal inner surface of the exchanger must be sufficient to properly adhere the powdered solids during the step of depositing the powdered solids on the deposited liquid adhesive. The thickness of the adhesive layer is for example between 5 μm and 50 μm.

[0040] According to the invention, the particle size of the powdered solid cannot be too large so that the weight of the particles remains compatible with the bonding strength of the liquid binder. Too large a particle size would result in a powder that is too heavy and thus cannot properly adhere to the surface of the exchanger cavity. Therefore, the maximum particle size of the powdered solid is selected based on the density of the powdered solid, the bonding strength of the binder and the thickness of the binder on the metal inner surface.

[0041] In addition, since the cross section of the internal cavity is 1mm 2 Up to 40mm 2 The particle size of the powdered solids must be kept limited in order not to excessively reduce the cross-section of the process fluid flowing through the exchanger cavity during operation of the exchanger.

[0042] In addition, a small particle size of the powdered solid is preferred because this increases the exchange surface area of ​​the coating resulting from the presence of the particles and thus enhances the effect of the powdered solid. Taking into account the morphology of the particles, the effective surface area of ​​the powdered solid is much greater than the effective surface area of ​​the metallic inner surface of the exchanger it covers.

[0043] The particle size of the powdered solid is adjusted beforehand by grinding and filtering to obtain a suitable particle size distribution. A high energy mill or attritor may be used to obtain a small particle size.

[0044] According to one example of the invention, the step of depositing the liquid adhesive on the metal inner surface is performed by immersing the exchanger in a bath of the liquid adhesive until the cavity is filled or by circulating the liquid adhesive through the cavity.

[0045] Dipping is a simple way to coat the metal inner surface of an exchanger. The exchanger is placed in a bath in an orientation that allows the air in the exchanger cavity to be evacuated and filled with liquid adhesive. This prevents air from being trapped in the heat exchanger, resulting in an uncoated surface. The heat exchanger is kept in the bath for the time required to fill it, for example about 10 minutes.

[0046] Alternatively, the exchanger can be placed so that its cavity is arranged vertically, or tilted with a main vertical component, and the liquid adhesive is poured into the exchanger from the top of the exchanger so that the liquid flows into the exchanger cavity by gravity flow. The lower part of the exchanger can be blocked so that the liquid adhesive can be fed into the exchanger. The lower part of the exchanger can remain free so that any excess liquid (which does not adhere to the inner surface of the exchanger) leaves the exchanger through the lower end of the exchanger. The amount of the adhesive poured must be enough to ensure that the adhesive is deposited on all inner surfaces of the exchanger that need coating.

[0047] Once the metal interior surface has been coated with the binder, the powdered solid is deposited.

[0048] In one embodiment of the present invention, the step of depositing the powdered solid on the deposited adhesive is performed by feeding or pouring. For example, gravity discharge can be used. As with adhesive deposition, the exchanger is then placed so that its cavity is arranged vertically, or tilted with a main vertical component, and the powder of the powdered solid is poured into the exchanger from the top of the exchanger so that the powder flows into the exchanger cavity. Alternatively, the feeding of the powder can be carried out when the lower end of the exchanger is blocked. In this case, the amount of the powder poured must be sufficient to ensure that the powder is deposited on all metal inner surfaces of the exchanger that need coating.

[0049] According to another embodiment of the invention, the step of depositing the powdered solid on the deposited binder is performed by placing the exchanger in a fluidizing chamber in which the powdered solid has been pre-suspended using a gas.

[0050] It would be very difficult, if not impossible, to immerse the exchanger in a tank simply containing powdered solids, as the mechanical resistance to the displacement of the powder would be too great. By analogy, imagine how difficult it would be to immerse the exchanger in a sandbox.

[0051] By fluidizing the powdered solid, it behaves like a liquid. The heat exchanger can then be immersed in the fluidized bed until it is completely covered. Fluidization also promotes the flow of powder into the internal cavity of the exchanger. The exchanger can be placed in a housing with its cavity arranged vertically, or tilted with a predominantly vertical component to promote the flow of powder through the exchanger.

[0052] By adjusting the descent speed of the exchanger in the fluidizing chamber, the cavity is coated with a uniformly distributed layer of powdered solid particles. The coverage of the metal inner surface by the powdered solid is thus very high, exceeding the target minimum of 60%.

[0053] As in the previous methods, the chamber in which the exchanger is immersed can be a thermostatically controlled fluidizing chamber for the polymerization of the binder.

[0054] Advantageously, the gas used to suspend the powdered solid comprises an agent that interacts with the powdered solid.

[0055] Advantageously, the agent is designed to initiate or accelerate the polymerization of the binder. The agent is, for example, nitrogen hydride to reduce or control the moisture content of the powdered solid.

[0056] The present invention makes it possible to obtain a consistent coating of powdered solids on all the metal inner surfaces of the exchanger by using a high flowability liquid binder that completely covers all the metal inner surfaces of the exchanger and a small particle powder whose deposition method enables all previously deposited binder to be covered. This provides a large surface area of ​​the solid where the catalyst promotes the desired physicochemical reaction.

[0057] According to a second aspect of the present invention, a cryogenic heat exchanger is proposed, characterized in that the cryogenic heat exchanger comprises a metal inner surface coated with a coating, which serves as a catalyst for the physicochemical reaction performed according to the first aspect of the present invention.

[0058] Advantageously, the metallic inner surface of the exchanger forms a cavity with an aspect ratio equal to or greater than 1000.

[0059] According to one embodiment of the invention, the exchanger is made of aluminum or an aluminum alloy and the powdered solid is an oxide, a hydroxide, a mixture of oxides or hydroxides, or a mixture of oxides and hydroxides.

[0060] Advantageously, the oxide is Fe 2 O 3 or the hydroxide is Fe(OH) 3 .

[0061] The invention is particularly advantageous for cryogenic exchangers of the brazed plate-corrugated type for hydrogen production, in which the coating of the metal inner surface obtained according to the invention acts as a catalyst for the physicochemical reaction of the conversion of normal-parahydrogen. This conversion is carried out when the hydrogen is liquid and at a temperature of about -250°C. BRIEF DESCRIPTION OF THE DRAWINGS

[0062] Additional features and advantages of the present invention will become apparent from the following detailed description, which can be understood with reference to the accompanying drawings, in which:

[0063] Figure 1 is a schematic diagram of a coating method according to a second embodiment of the present invention;

[0064] Figure 2 is Figure 1 A partial schematic diagram of a low-temperature plate heat exchanger according to one embodiment of the present invention after step C of the coating method shown;

[0065] Figure 3 is Figure 1 Step D of the coating method shown is then similar to Figure 2 's view;

[0066] Figure 4 is Figure 1 Step F of the coating method shown is then similar to Figure 3 a view of

[0067] Figure 5 is a partial schematic diagram of an exchanger according to the invention to illustrate the ratio between the width and the length of its internal cavity.

[0068] like Figure 1 As shown, in step A, first, the powder of the powdered solid as a catalyst to be deposited on the metal inner surface of the heat exchanger 1 is subjected to particle size adjustment by mechanical grinding, and then dry filtration is performed to obtain and retain only particles of a suitable particle size.

[0069] In step B, the obtained powder is placed in a fluidizing chamber, in which a fluidized bed is formed by the circulation of a gas.

[0070] In parallel, step C prepares the exchanger 1, the inner surfaces of which form the substrate or wall to be coated. These surfaces can be etched with a liquid acid solution to ensure perfect bonding of the adhesive and the powdered solid. Figure 2 A close-up partial section of the exchanger 1 after this step C is shown. The corrugations 2 are arranged between two baffles 3. The corrugations 2 and the baffles 3 form a cavity 10 having a metallic inner surface 11 .

[0071] Then, in step D, the adhesive is applied to the surface of the cavity 10 by dipping in this example. The exchanger 1 is thus immersed in a bath of liquid adhesive at an angle so that the air in the exchanger 1 can escape and be replaced by the liquid adhesive. The bath temperature can be controlled to obtain a given adhesive viscosity, for example 1×10 at 20° C. -3 The exchanger 1 is then removed from the adhesive bath and held above the adhesive bath by arranging the exchanger 1 with its cavity oriented vertically. Thus, excess adhesive drains from the exchanger 1 by gravity and falls into the bath. Figure 3 It shows that after step D Figure 2 The inner surface of the exchanger 1 is covered with an adhesive 4.

[0072] The exchanger 1 is then immersed in the fluidized bed in phase E. Advantageously, the descent speed of the exchanger 1 in the fluidized bed is chosen to be between 0.5 mm / s and 1 m / s and more preferably between 1 mm / s and 10 mm / s.

[0073] Exchanger 1 remained in the fluidized bed for a few minutes and was then removed.

[0074] Advantageously, the withdrawal speed of the exchanger 1 from the fluidized bed is chosen to be between 0.5 mm / s and 1 m / s and more preferably between 1 mm / s and 10 mm / s.

[0075] The excess powder is then removed in step F, which in this example occurs when the exchanger 1 leaves the fluidized bed. The exchanger 1 is arranged with its chamber 10 oriented vertically above the powder container. The particles that are not held by the binder therefore flow out of the exchanger 1 by gravity. To promote this flow, the exchanger 1 can be gently shaken and / or gas can be injected into the exchanger 1 to mechanically entrain the loose particles. Figure 4 It shows that after step F Figure 3 Particles 5 of powdered solid are held on the inner surface of the exchanger 1 by a binder.

[0076] Please note that the drawings schematically show an exemplary embodiment of the invention. The ratios between the sizes of the elements shown do not necessarily represent actual ratios. Thus, compared to the sizes of the waves and baffles and the cavities they form, Figure 4The size of the mesoparticles 5 and the thickness of the binder 4 do not necessarily represent their actual sizes.

[0077] In step G, the exchanger 1 is then placed in a thermostatic chamber where it can be heated to 150° C. for several tens of minutes in order to polymerize the adhesive.

[0078] In step H, the exchanger 1 is removed from the thermostatic chamber and brought back to ambient temperature.

[0079] Figure 5 A schematic diagram of an exchanger 1 according to the invention is shown. The distance 6 represents the width of the cavity and the distance 7 represents the length of the cavity. According to the invention, the catalyst-coated cavity of the exchanger 1 has a length / width ratio equal to or greater than 1000. As shown in the enlarged view 8b of the circular portion 8a of the exchanger 1, the corrugations 2 form with the partitions 3 a cavity 10 with a width of 6 and a height of 9. To calculate the ratio between the width and the length of the cavity, the width of the cavity is taken as the smaller of its width or height. In this example, the length / width ratio is 7 / 6.

Claims

1. A method for producing a coating on the inner surface of a metal forming a cavity of a heat exchanger, the coating being intended to act as a catalyst for the physicochemical reaction of the normal-secondary conversion of hydrogen, characterized in that it comprises the following successive steps: - a step of depositing a liquid binder on the inner surface of the metal, the liquid binder being water-based, organic or inorganic, and - A step of depositing a powder of a powdered solid on the deposited liquid binder, said powdered solid being a mineral and said powder having a particle size between 10 μm and 100 μm.

2. The method according to claim 1, characterized in that The method comprises, after the powder deposition step, a subsequent step of maintaining the inner surface at ambient temperature, during which the solvent of the liquid binder is at least partially removed by evaporation.

3. The method according to claim 1, characterized in that The method comprises, after the powder deposition step, a subsequent step of polymerizing the liquid binder by a heat treatment carried out in a temperature range that does not allow the inner surface to interact with the powdered solid.

4. The method according to claim 3, characterized in that The heat treatment is performed at a temperature of 200°C or less.

5. The method according to claim 2 , wherein: During the subsequent step of maintaining the inner surface at ambient temperature, an air flow is generated in the exchanger cavity, during which the solvent in the liquid binder is at least partially removed by evaporation; or during the subsequent step of polymerizing the liquid binder by a thermal treatment in a temperature range that does not allow the inner surface to interact with the powdered solid, an air flow is generated in the exchanger cavity.

6. The method according to claim 2, characterized in that After the step of removing the powder of the powdered solids that do not adhere to the liquid binder deposited on the inner surface of the exchanger, the subsequent step of maintaining the inner surface at ambient temperature is carried out, during which the solvent in the liquid binder is at least partially removed by evaporation; or the subsequent step of polymerizing the liquid binder by a heat treatment in a temperature range that does not allow the metal inner surface to interact with the powdered solids is carried out.

7. The method according to claim 1, characterized in that The liquid binder is polyvinyl alcohol and / or a polymer.

8. The method according to claim 1, characterized in that The liquid adhesive has a viscosity comparable to that of water, i.e., 1×10 -3 Pa.s.

9. The method according to claim 1, characterized in that The liquid adhesive has sufficient wettability on the inner surface to leave an adhesive layer on the inner surface after the liquid adhesive contacts the inner surface.

10. The method according to any one of the preceding claims, characterized in that The exchanger is made of aluminum or an aluminum alloy, and the powdered solid is an oxide, or a hydroxide, or a mixture of oxides and hydroxides, or a mixture of oxides and hydroxides.

11. The method according to claim 10, characterized in that The oxide is Fe2O3 or the hydroxide is Fe(OH)3.

12. The method according to any one of claims 10 or 11, characterized in that The powder of the powdered solid has a particle size between 50 nm and 1 μm.

13. The method according to any one of claims 1 to 9, characterized in that The step of depositing liquid adhesive on the metal inner surface is performed by immersing the exchanger in a bath of liquid adhesive until the cavity is filled or by circulating liquid adhesive through the cavity.

14. The method according to claim 1, characterized in that The step of depositing the powder of the powdered solid onto the deposited binder is performed by feeding or pouring.

15. The method according to claim 1, characterized in that Said step of depositing said powdered solid on the deposited binder is performed by placing said exchanger in a fluidizing chamber in which said powdered solid has been pre-suspended using a gas.

16. The method according to claim 15, characterized in that The gas used to suspend the powdered solid includes an agent that interacts with the powdered solid.

17. The method according to claim 16, characterized in that The agent is intended to initiate or accelerate the polymerization of the adhesive.

18. A low temperature heat exchanger, characterized in that: The low temperature heat exchanger comprises a metal inner surface coated with a coating which acts as a catalyst for a physicochemical reaction performed according to any one of claims 1 to 17.

19. The heat exchanger according to claim 18, characterized in that The metal inner surface forms a cavity, and the aspect ratio of the cavity is greater than or equal to 1000.

Citation Information

Patent Citations

  • Method for depositing a corrosion-protection coating

    EP2956566A1

  • Method for depositing an Anti-corrosion coating

    EP3049545A1